Risk factors for scabies, tungiasis, and tinea infections among schoolchildren in southern Ethiopia: A cross-sectional Bayesian multilevel model - Amare, Hiwot Hailu; Lindtjorn, Bernt (PLOS Neglected Tropical Diseases, 2021)
Author summary Skin problems are common disorders in resource poor settings. Scabies and tungiasis are neglected tropical diseases causing significant sickness in communities with poor living conditions. Scabies is dermatosis caused by a burrowing mite, Sarcoptes scabiei var. hominis. Tungiasis is caused by a flea, Tunga penetrans, infesting the skin, usually on the feet or hands. Tinea infection is a fungal dermatophyte infection of the skin and the most common dermatological problem among schoolchildren in Ethiopia, especially tinea capitis. Application of a Bayesian approach to identify possible risk factors for these problems has seldom been used. We found that compared to the frequentist model, the Bayesian model better explained school- and classroom-level variations in skin problems among schoolchildren. Our findings also suggest that transmission of skin infections, especially fungal and scabies infections, frequently occurs in schools and classrooms. We identified several risk factors for these conditions, including low socioeconomic status; unclean fingernails; not washing with soap at least every week; and sharing beds, clothes, and combs. Thus, it is important to improve the personal hygiene of schoolchildren through education. Regular checkups by teachers also can improve skin health and related morbidity in rural schoolchildren in southern Ethiopia.